IMF Involvement in International Trade Policy Issues. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2009)
Trade policy occupies an unusual and at times problematic place in the work of the IMF. Though trade policies of IMF members have strong influences on macroeconomic stability, they are often seen as peripheral to the IMF's core competency. This evaluation, which examines the IMF's involvement in trade policy issues during 1996-2007, addresses five questions. What is the nature of the IMF's mandate to cover trade policy? Did the IMF work effectively with other international organizations on trade policy issues? Did the Executive Board provide clear guidance to staff on the IMF's role and approach to trade policy? How well did the IMF address trade policy issues through lending arrangements and surveillance? Was IMF advice effective? The evaluation finds that the IMF's role in trade policy has evolved in some desirable and some less desirable ways and recommends how to use the limited resources the IMF can devote to trade policy to fill these gaps.